2012
DOI: 10.1111/j.2041-1014.2012.00637.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of CiaRH with resistance of Streptococcus mutans to antimicrobial peptides in biofilms

Abstract: Streptococcus mutans is a cariogenic pathogen in humans. To persist in the oral cavity, S. mutans is resistant against several antibacterial factors derived from the host. In this study, we investigated the mechanism of resistance to cationic antimicrobial peptides (AMPs), which are innate immune factors in humans. Because dltA-D (teichoic acid biosynthesis) was reported to affect the susceptibility to AMPs in other bacterial species, we evaluated the susceptibility of a dltC knockout mutant of S. mutans to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 38 publications
(82 reference statements)
1
25
0
Order By: Relevance
“…In our study, 3 of the 15 TCSs identified in S. mutans were demonstrated to be associated with resistance to human- or bacteria-derived antimicrobial peptides [55], [59]. Furthermore, other researchers reported that 3 additional TCSs were associated with production of or resistance to antibacterial agents [48], [60], [61].…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…In our study, 3 of the 15 TCSs identified in S. mutans were demonstrated to be associated with resistance to human- or bacteria-derived antimicrobial peptides [55], [59]. Furthermore, other researchers reported that 3 additional TCSs were associated with production of or resistance to antibacterial agents [48], [60], [61].…”
Section: Discussionsupporting
confidence: 52%
“…As a result of this comprehensive analysis, one TCS ( ciaRH ) knockout mutant showed increased susceptibility to LL37 and beta-defensins (HBD1-3) in biofilm cells [55]. Further experiments showed that CiaRH regulates the dlt operon, which plays an important role in the acquisition of resistance to positively-charged antimicrobial agents, such as LL37 and β-defensins.…”
Section: Association Of Tcs With Antimicrobial Susceptibility In S Mmentioning
confidence: 90%
“…The primers used are shown in Table 2. Since the DNA gyrase A subunit (gyrA) was stably expressed and used as the internal control for quantitative PCR (32,33), the amount of gyrA was used as an internal control in this study. Three independent experiments were performed, and the means Ϯ standard deviations (SD) were calculated.…”
Section: Methodsmentioning
confidence: 99%
“…The susceptibility of S. mutans to AMPs has been reported to be regulated by dltC gene expression in biofilm cells [65]. …”
Section: Antibiofilm Peptide Applications In Cariologymentioning
confidence: 99%